Zentren für seltene Erkrankungen - Grüters-Kieslich, Annette; Burgard, Peter; Berner, Reinhard; Hoffmann, Georg F. (Monatsschrift Kinderheilkunde, 2017)
The national action plan elaborated by the National Action League for People with Rare Diseases (NAMSE) includes as a key measure the establishment of centers for rare diseases. With the support of the Innovation Fund from April 2017 until March 2020 nine pediatric university hospitals will implement this measure and evaluate its efficacy. In general disease (NAMSE type A centers) and disease-specific competence areas (NAMSE type B centers), cross-sector, IT-assisted patient pathways will be implemented. The centers for rare diseases form a network which, through support from specific expert panels, aims at interregional improvement in the quality of interdisciplinary diagnostics and the treatment of rare diseases. The participation of experts in cross-site case conferences will ensure that patients benefit from all currently available expertise in the field of undiagnosed as well as specific rare disease patterns. Innovative genetic diagnostics will be carried out based on the indications established by an expert panel and with validation by the relevant physicians so ensuring the highest quality. The treatment of patients with selected indicator diagnoses, e. g. diseases that are detected in newborn screening, will be enhanced through interdisciplinary case management, case conferences, access to precise diagnostics and therapy as well as by a structured transition from pediatrics to adult medicine with the aim of achieving better treatment quality and sustainability. Improved communication with primary care providers is achieved by IT-based access to updated patient hospital data so that any delays, for example in implementing or tailoring therapy, can be avoided.